2015
DOI: 10.1039/c4tx00174e
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of chemical aquatic toxicity with chemical category approaches and substructural alerts

Abstract: Aquatic toxicity is an important endpoint in the evaluation of chemically adverse effects on ecosystems.In this study, in silico models were developed for the prediction of chemical aquatic toxicity in different fish species. Firstly, a large data set containing 6422 data points on aquatic toxicity with 1906 diverse chemicals was constructed. Using molecular descriptors and fingerprints to represent the molecules, local and global models were then developed with five machine learning methods based on three fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…47 Several groups of SAs have been reported for different toxic endpoints. 16,34,35,[49][50][51][52][53][54] We identied the privileged substructures responsible for DILI with substructure fragment analysis 50 methods based on KRFP ngerprints. If a substructure presented more frequently in DILI-positive chemicals than DILI-negative chemicals, this substructure would be regarded as a privileged substructure.…”
Section: Identication Of Privileged Substructures or Structural Alertsmentioning
confidence: 99%
“…47 Several groups of SAs have been reported for different toxic endpoints. 16,34,35,[49][50][51][52][53][54] We identied the privileged substructures responsible for DILI with substructure fragment analysis 50 methods based on KRFP ngerprints. If a substructure presented more frequently in DILI-positive chemicals than DILI-negative chemicals, this substructure would be regarded as a privileged substructure.…”
Section: Identication Of Privileged Substructures or Structural Alertsmentioning
confidence: 99%
“…Fishes are usually used as model species to evaluate aquatic toxicity and avian species are widely used as model species to evaluate the terrestrial toxicity. Our group previously collected LC 50 data of three fish species from ECOTOX database and built several local and global models (Sun et al, 2015 ). Recently, we reported a model focusing on the aquatic toxicity of pesticides and found that the molecule fingerprints performed different between local and global models (Li et al, 2017 ).…”
Section: Progress In Toxicity Predictionmentioning
confidence: 99%
“…A QSAR is a regression or a classification model that relates chemical structures to their biological activities by means of mathematical and statistical modeling. Although there is extensive QSAR literature for rainbow trout toxicity (particularly acute) on industrial organic chemicals , there is only 1 report on the single and combined toxicity of PPCPs on the RTL‐W1 cell line . In their work, Schnell et al assessed the cytotoxicity of different PPCPs together with their mixtures on RTL‐W1 cell lines by using Alamar Blue and CFDA‐AM fluorescent dyes, respectively.…”
Section: Introductionmentioning
confidence: 99%